STUDY OF COMPLICATIONS AND EFFECTS OF LAPAROSCOPIC SPLENECTOMY - Kaisser Salah Yakoop; Shaimaa Abd Ali Ghani; Suha Abdulqader Abdulsattar (Scholar Express Journals, 2021)
This paper focuses on the knowledge of the Complications and Effects of laparoscopic splenectomy, where 100 patients were collected from Teaching Hospital, Baghdad, Iraq, where the average age through real value extraction and standard regression was 39 ± 3.3 for men, who were 60 patients, and for women, the average age was 38.3 ±4.5 with 40 patients The spleen was removed and during this operation 3 to 4 small holes are made in the abdomen through which the spleen is removed. It is preferred because it results in a small wound, the operation is less painful and the patient can leave the hospital within a day or two In some cases of spleen enlargement or disease, the treatment is to eradicate it. This eradication has no effect on the body in general. A person can live without the spleen a normal life. Among the diseases or problems that require the removal of the spleen as a result of an accident or a strong blow to it, and this usually results in severe bleeding from the spleen. ITP (Idiopathic Thrombocytopenic Purpura,): This disease is considered one of the most common reasons for spleen removal, and in this disease there are antibodies from the spleen that break platelets in the blood
Keywords: LAPAROSCOPIC; SPLENECTOMY; Complications; diseases